Apologetics without apology : speaking of God in a world troubled by religion - Graham, Elaine L. (Eugene, Oregon : Cascade Books, 2017)
Against many expectations, religion has not vanished from Western culture. People are troubled and fascinated in equal measure by this new visibility and are unsure whether it is right to (re)incorporate the vocabulary of faith into our common life. This unprecedented co-existence of religion and secularism is sometimes termed the ""postsecular, "" and in this book Elaine Graham considers some of its implications for the public witness of Christianity. She argues that everyone, from church leaders, theologians, local activists, and campaigners, needs to learn again how to ""speak Christian"" in.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 186.
Description based on electronic record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Apologetics; Apologetics; RELIGION / Christian Theology / Apologetics; Electronic books